Efficacy and safety of morphine and methadone as analgesics in a balanced anaesthetic protocol in rabbits - Nobre, Camila Vieira; Uscategui, Ricardo A.R.; Noriega, Jorge; Gasser, Beatriz [UNESP]; Pazzini, Josiane Morais; de Almeida, Vívian Tavares [UNESP]; de Nardi, Andrigo Barboza [UNESP]; de Andrade, James Newton (Universidad Nacional Mayor de San Marcos, Vicerectorado de Investigacion, 2022)
The efficacy of preventive analgesia and the cardiopulmonary effects of morphine or methadone in rabbits undergoing experimental skin surgery were evaluated and compared. Thirty-six rabbits were randomly assigned to three experimental groups: Control, Morphine, and Methadone. The rabbits received midazolam 1 mg/kg IM associated with: placebo (NaCl 0.9%) 0.05 ml/kg, methadone 0.5 mg/kg or morphine 0.5 mg/kg, depending on the experimental group. Anaesthesia was induced and maintained with isoflurane. Heart (HR) and respiratory (fR) rates, peripheral oxygen saturation (SpO2), mean arterial pressure (MAP), and body temperature were assessed every 10 minutes. Electrocardiographic examination was performed after sedation, in the trans and immediate postoperative period. After procedure, the control group received tramadol 5 mg/kg IV. Postoperative analgesia was assessed using the visual analogue scale (VAS) and Von-Frey filament stimulation responses. All variables were compared between groups by ANOVA or Friedman. Methadone and morphine caused an increase in MAP (p=0.0112) and a decrease in HR (p=0.0001). fR and SpO2 were reduced in the methadone group (p=0.0100). The response to Von-Frey filaments (p=0.6824) and VAS (p=0.7661) were similar between treatments, however, the control group presented a higher proportion of analgesic rescue (33%) compared to morphine (19%) and methadone (12%). Electrocardiographic variables were similar between treatments (p>0.05). In conclusion, preventive treatment with morphine or methadone was effective in controlling trans and postoperative pain in rabbits, and its cardiovascular effects were limited; however, methadone caused marked respiratory depression.
Eficacia y seguridad de morfina y metadona como analgésicos en un protocolo anestésico balanceado en conejos
Keywords: analgesia; analgesic rescue; methadone; morphine; respiratory depression